2004
DOI: 10.1523/jneurosci.1746-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mate Searching inCaenorhabditis elegans: A Genetic Model for Sex Drive in a Simple Invertebrate

Abstract: Much of animal behavior is regulated to accomplish goals necessary for survival and reproduction. Little is known about the underlying motivational or drive states that are postulated to mediate such goal-directed behaviors. Here, we describe a mate-searching behavior of the Caenorhabditis elegans male that resembles the motivated behaviors of vertebrates. Adult C. elegans males, if isolated from mating partners, will leave the area of a food source and wander about their environment in an apparent search for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
305
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(319 citation statements)
references
References 41 publications
13
305
1
Order By: Relevance
“…Taken together, these data demonstrate that TMC-1 has a developmental effect, (and to a lesser extent, an acute effect) on repressing both appetitive (mating drive) and consumatory (spicule insertion) sexual behaviours on CeMM. Mutations in insulin and serotonin pathway genes have been shown to perturb development and mating, in a bacterial food source 35,49 , whereas our results showed that the tmc-1 mutation displayed an opposite effect, which accelerates larval development and male mating on CeMM.…”
Section: Tmc-1 Functions To Retard Growth On Cemmcontrasting
confidence: 63%
“…Taken together, these data demonstrate that TMC-1 has a developmental effect, (and to a lesser extent, an acute effect) on repressing both appetitive (mating drive) and consumatory (spicule insertion) sexual behaviours on CeMM. Mutations in insulin and serotonin pathway genes have been shown to perturb development and mating, in a bacterial food source 35,49 , whereas our results showed that the tmc-1 mutation displayed an opposite effect, which accelerates larval development and male mating on CeMM.…”
Section: Tmc-1 Functions To Retard Growth On Cemmcontrasting
confidence: 63%
“…First, a long-range pheromone acts to attract males (Chasnov et al, 2007). Next, a short-range and short-lived hermaphrodite signal triggers male searching behavior (Lipton et al, 2004). A distinct, diffusible hermaphrodite cue influences male locomotion (Simon and Sternberg, 2002).…”
Section: Elegans Male Sexual Behavior and The Turning Step Of Malementioning
confidence: 99%
“…Similarly, although a major regulator of worm behavior and development is levels of the constitutively produced dauer pheromone [8][9][10][107][108][109], the neurons that respond to pheromone are also not yet defined. Presumably, males and hermaphrodites also produce signals to attract or repel each other, but these cues and the relevant sensory neurons are unknown [3,4]. As "...behavior is messy" (with apologies to [110]), the development of technologies for imaging neuronal activity in single neuron types in vivo in response to an applied stimulus [111][112][113][114][115] may allow for more precise functional mapping of chemicals to sensory neuron types.…”
Section: Mapping Chemicals To Chemosensory Neuronsmentioning
confidence: 99%
“…For the sake of brevity, I will concentrate solely on these behaviors in the hermaphrodite. I refer the reader to several excellent publications and references therein addressing C. elegans male chemosensory behaviors [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%